FACTORS INFLUENCING THE EFFICIENCY OF THERAPY IN PATIENTS WITH RHEUMATOID ARTHRITIS: THE ROLE OF COMORBID MENTAL AND SOMATIC DISEASES - A. A. Abramkin; T. A. Lisitsyna; D. Yu. Veltishchev; O. F. Seravina; O. B. Kovalevskaya; S. I. Glukhova; E. L. Nasonov (Научно-практическая ревматология)
The response rate to therapy for rheumatoid arthritis (RA) rarely exceeds 60%. Mental disorders (MDs) of the anxiety-depressive spectrum (ADS) and cognitive impairment (CI) substantially affect the evaluation of the efficiency of RA therapy. Adequate psychopharmacotherapy is one of the possible approaches to optimizing the treatment of RA. The factors influencing the efficiency of RA therapy with standard disease-modifying antirheumatic drugs (DMARDs) and biological agents (BAs) in combination with adequate psychopharmacotherapy have not been previously identified. Objective: to determine the predictors of response to therapy in patients with RA receiving DMARDs and BAs with or without adequate psychopharmacotherapy for ADS disorders. Subjects and methods. The investigation included 128 patients (13% men and 87% women) with a reliable diagnosis of RA. At baseline, 75.1% of patients received DMARDs; 7.8% – BAs. ADS disorders were detected in 123 (96.1%) patients. Psychopharmacotherapy was offered to all the patients with MDs; 52 patients agreed to treatment and 71 refused. The following therapeutic groups were identified according to the performed therapy: 1) DMARDs (n = 39); 2) DMARDs + psychopharmacotherapy (n = 43); 3) DMARDs + BAs (n = 32); 4) DMARDs + BAs + psychopharmacotherapy (n = 9). The changes of MDs symptoms and the outcomes of RA were assessed in 83 (67.5%) patients at five-year follow-up. The efficiency of RA therapy was evaluated with DAS28 (EULAR criteria). Predictors of response to therapy were determined using linear regression modeling. Results and discussion. At 5 years, 22 (26.5%) and 37 (44.6%) patients were recorded to show good and moderate responses to therapy, respectively; 24 (28.9%) patients were non-respondents. The linear regression model included 14 factors (p<0.001). The high values of DAS28 (β=0.258) at the inclusion; belonging to therapeutic groups 2 (β=0.267), 3 (β=0.235), and 4 (β=0.210), the absence of diabetes mellitus (β=-0.230), and experience in using glucocorticoids (β=-0.230) were associated with a high likelihood of response to therapy; high body mass index (β=-0.200) and long RA duration (β=-0,181), a high level of rheumatoid factor (β=-0.176), a history of myocardial infarction (β=-0.153), schizotypic disorder (β=-0.132), and extra-articular manifestations of RA (β=-0.106), and older age (β=-0.102) were related to a low probability of response. The area under the ROC curve for the model was 0.99 (p><0.001). Conclusion. BA therapy and psychopharmacotherapy, along with younger age, shorter duration and high activity of RA, a low level of rheumatoid factor, lower body mass index, the absence of diabetes mellitus, myocardial infarction, and extra-articular manifestations of RA in the history, schizotypic disorder, and experience in using glucocorticoids are associated with a greater likelihood of a good and moderate treatment response. Keywords: rheumatoid arthritis; mental disorders; disease-modifying antirheumatic drugs; biological agents; efficiency of therapy; predictors; psychopharmacotherapy; therapy adherence><0.001). The high values of DAS28 (β=0.258) at the inclusion; belonging to therapeutic groups 2 (β=0.267), 3 (β=0.235), and 4 (β=0.210), the absence of diabetes mellitus (β=-0.230), and experience in using glucocorticoids (β=-0.230) were associated with a high likelihood of response to therapy; high body mass index (β=-0.200) and long RA duration (β=-0,181), a high level of rheumatoid factor (β=-0.176), a history of myocardial infarction (β=-0.153), schizotypic disorder (β=-0.132), and extra-articular manifestations of RA (β=-0.106), and older age (β=-0.102) were related to a low probability of response. The area under the ROC curve for the model was 0.99 (p<0.001). Conclusion. BA therapy and psychopharmacotherapy, along with younger age, shorter duration and high activity of RA, a low level of rheumatoid factor, lower body mass index, the absence of diabetes mellitus, myocardial infarction, and extra-articular manifestations of RA in the history, schizotypic disorder, and experience in using glucocorticoids are associated with a greater likelihood of a good and moderate treatment response. Keywords: rheumatoid arthritis; mental disorders; disease-modifying antirheumatic drugs; biological agents; efficiency of therapy; predictors; psychopharmacotherapy; therapy adherence><0.001). Conclusion. BA therapy and psychopharmacotherapy, along with younger age, shorter duration and high activity of RA, a low level of rheumatoid factor, lower body mass index, the absence of diabetes mellitus, myocardial infarction, and extra-articular manifestations of RA in the history, schizotypic disorder, and experience in using glucocorticoids are associated with a greater likelihood of a good and moderate treatment response.